The use of Finding Nemo Movie to Improve Vocabulary Mastery of the Seventh Grade Students of SMPN 17 Semarang in Academic Year 2023/2024 - Siti Nur Zulaihah; Jafar Sodiq; Arso Setyaji (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This study examines the effectiveness of using the "Finding Nemo" movie to improve the vocabulary skills of seventh-grade students of SMPN 17 Semarang. Using a quantitative and pre-experimental method, the study aims to evaluate vocabulary improvement before and after using the movie and determine any significant differences between the two. The sample consists of 30 students. Results show that the average pre-test score was 62.00, while the post-test score was 78.00. At a 0.05% significance level, the t-score was less than the t-table, leading to the acceptance of the alternative hypothesis and the rejection of the null hypothesis. In conclusion, there is a significant difference in students' vocabulary skills after using the "Finding Nemo” movie."